Potential of biocompatible calcium-based metal-organic frameworks for the removal of endocrine-disrupting compounds in aqueous environments - Sukatis, Fahren Fazzer; Wee, Sze Yee; Aris, Ahmad Zaharin (Elsevier, 2022)
Rapid urbanization, industrialization and population growth have accelerated the amount and variety of emerging contaminants being released into the aqueous environment, including endocrine-disrupting compounds (EDCs). The introduction of these compounds constitutes a threat to human health and the environment, even at trace levels. Hence, new water treatment technologies are urgently required to effectively remove EDCs from water. The currently available technologies used in water remediation processes are expensive and ineffective, and some produce harmful by-products. Calcium-based metal-organic frameworks (Ca-MOFs) are porous synthetic materials that can potentially be applied as adsorbents. These MOFs are hydrolytically stable, biocompatible and low-cost compared with conventional porous materials. The structure of Ca-MOFs is maintained even though calcium metal centers in the structure can easily coordinate with water. Ca-MOFs and their composite derivatives have the potential for use in water purification because these biocompatible adsorbents have been shown to selectively extract a significant quantity of contaminants. This review highlights the potential of Ca-MOFs to adsorb EDCs from aqueous environments and discusses adsorbent preparation methods, adsorption mechanisms, removal capacity, water stability and recyclability. This review will support future efforts in synthesizing new biocompatible MOFs as an environmental treatment technology that can effectively remove EDCs from water, thereby improving environmental and human health.